Workplace Training in Germany and Its Impact on Subjective Job Security: Short- or Long-Term Returns? - Bettina Kohlrausch; Anika Rasner (Journal of European Social Policy, 2014)
Based on data from the Socio-Economic Panel (SOEP) study, this article analyses the effects of workplace training in Germany on subjective job security. Using fixed-effects models, this article tests whether workplace training has positive effects on perceived job security, and if so, whether the returns are of a short- or long-term nature. The results confirm a positive effect of workplace training on perceived job security, not only in the short term but in the long term as well. The inclusion of interaction terms for different levels of education shows that low-educated individuals benefit most from participation in workplace training. The immediate effect on subjective job security is strongest, and the post-training effect is most sustained for this group compared to those with higher levels of education. Lower-educated employees often lack access to workplace training, however. The authors conclude that workplace training has the potential to be a mutually beneficial investment for both employers and employees. More targeted policy incentives should aim at enhancing access to workplace training, most importantly for the loweducated, as for them training might be an effective means for improved employment prospects.
Additional information: Dieser Beitrag ist mit Zustimmung des Rechteinhabers aufgrund einer (DFG-geförderten) Allianz- bzw. Nationallizenz frei zugänglich. - This publication is with permission of the rights owner freely accessible due to an Alliance licence and a national licence (funded by the DFG, German Research Foundation) respectively.
Keywords: 330; Germany; International Standard Classification of Education–1997; Socio-Economic Panel; subjective job security; workplace training; Betriebliches Bildungsmanagement; Beschäftigungssicherung; Deutschland